j=-6

Simple and best practice solution for j=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for j=-6 equation:



j=-6
We move all terms to the left:
j-(-6)=0
We add all the numbers together, and all the variables
j+6=0
We move all terms containing j to the left, all other terms to the right
j=-6

See similar equations:

| (x+1)^3=25 | | 6/x2-9-1/x-3=1/x+3 | | 10w-9=-8+3w | | 2x+4x+7=-3x | | 5y+9=-9-3y | | 5x/x-3=3x+6/x-3 | | 5y+9=(-9-3y) | | -3t^2+12t+36=0 | | 8/3d+4/3d=2 | | .75x-7=2.80 | | 1.21x+11.87=x+12.50 | | 0.006(9-k)+0.04(k-4)=1 | | 0.006(9−k)+0.04(k−4)=10.006(9-k)+0.04(k-4)=1 | | 11+3x=-14 | | x-16=360 | | x+16=360 | | 0.3(x+1632)=726 | | 32x-5)=2x+5 | | 2^{3x+1}=5 | | 5x+(-12x+24)=11 | | n–4=-12 | | X.x+4=-1.5x-21 | | 8=3o-1 | | (x+2)/3-40=-37 | | (x-8)/5+3=7 | | 3x+9=-80 | | 39.99+1.25x=25.99+1.75x | | -30-3z-z=48+2z | | -30-3z-z=48=2z | | 0.11x+0.6(x-4)=0.01(4x-2) | | 12+8y+y=2y+48=4y | | {x-2}{3}-5=-3 |

Equations solver categories